DESIGN OF HIGH EFFICIENCY MULTIPHASE CASCADED DC-DC BOOST CONVERTERS WITH INDUCTANCE OPTIMIZATION - Farras Muzakki, Muhammad
DESIGN OF HIGH EFFICIENCY MULTIPHASE CASCADED DC-DC BOOST CONVERTERS WITH INDUCTANCE OPTIMIZATION Muhammad Farras Muzakki ABSTRACT This study presents the design of a multiphase cascaded DC-DC boost converter which has high efficiency with optimization of inductance value. The multiphase cascaded DC-DC boost converter is a converter that has a very high gain level and low input current ripple. The paper begins with the derivation of the loss equation in the converter and the results are used for the optimization process. Previous research with the same converter has achieved an efficiency of 85.8%. The efficiency of the converter is increased by reducing the inductance so that the converter operates at the critical conduction mode (CRM) limit. The selection of this inductance will affect the resistance value of the inductor so that efficiency will increase. In addition, the winding manufacturing technique and the selection of the inductor core are also determined. The results of this inductor replacement resulted in the highest efficiency in CCM mode with an inductance of 0.3 mH which reached 89.19% in laboratory tests. While in critical mode, at 0.15 mH inductance, efficiency is 86.23%. Keywords— boost converter, multiphase, cascaded, inductance, critical conduction mode (CRM), continous conduction mode (CCM), optimization, efficiency.